2017
DOI: 10.3390/su9030406
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Local Governance: Effects on the Sustainability of Bioenergy Innovation

Abstract: This paper deals with processes and outcomes of sustainable bioenergy development in Emilia Romagna. It draws on an on-going research project concerning inclusive innovation in forest-based bioenergy and biogas in Norway, Sweden, Finland and Italy. The goal is to explore how local governance impacts on inclusive innovation processes and triple bottom sustainability of bioenergy development in Emilia Romagna and, ultimately, to contribute to the debate on the bioeconomy. It thus compares the case of biogas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
(113 reference statements)
0
19
0
Order By: Relevance
“…The comparison builds on the findings of the within‐case analysis (Cavicchi, ; Cavicchi, ; Cavicchi et al, ; Cavicchi et al, ; Cavicchi & Ely, ), the governance dimensions and interrelations between them highlighted in the pathways approach and power in transitions approach (Leach et al, ; Byrne et al, ; Cavicchi & Ely, ; Leach et al, 2010a; Stirling, ; Avelino & Wittmayer, ; Avelino, ; Avelino, ), and the system archetypes (Braun, ; Cavicchi, ; Kim, ; Senge et al, ; Wolstenholme, ; Cavana et al, ). The three governance dimensions are actors' framings, rules of the game, and power relations (Smith & Stirling, ; Smith, Stirling, & Berkhout, ).…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison builds on the findings of the within‐case analysis (Cavicchi, ; Cavicchi, ; Cavicchi et al, ; Cavicchi et al, ; Cavicchi & Ely, ), the governance dimensions and interrelations between them highlighted in the pathways approach and power in transitions approach (Leach et al, ; Byrne et al, ; Cavicchi & Ely, ; Leach et al, 2010a; Stirling, ; Avelino & Wittmayer, ; Avelino, ; Avelino, ), and the system archetypes (Braun, ; Cavicchi, ; Kim, ; Senge et al, ; Wolstenholme, ; Cavana et al, ). The three governance dimensions are actors' framings, rules of the game, and power relations (Smith & Stirling, ; Smith, Stirling, & Berkhout, ).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Therefore, on the one hand, we need to better understand the interdependence of social and environmental processes across scales (e.g., Cavicchi, 2016Cavicchi, , 2018Cavicchi & Ely, 2016); on the other hand, we need to look at the governance of the BES to understand what structural dynamics affect sustainable local development. On the basis of a previous within-case analysis (Cavicchi, 2016;Cavicchi, 2018;Cavicchi, Bryden, & Vittuari, 2014;Cavicchi & Ely, 2016;Cavicchi, Palmieri, & Odaldi, 2017), evidence shows that despite the contextual differences (e.g., geography, adopted technology, and biomass type and policies), the two regions share similar declining bioenergy production trends, policy objectives, discourses, and power relations. Thus, this comparison has the potential to shed light on the patterns of behavior of bioenergy governance configurations that impact on sustainable local development.…”
Section: Introductionmentioning
confidence: 99%
“…Cambero and Sowlati [31] concluded that no studies have incorporated social factors into their assessments, implying that incorporating them is quite challenging. Nonetheless, social factors are indeed critical to ensure sustainable wood energy, particularly in rural areas where various factors other than economic ones play relatively important roles [39,40]. We recognize the need to include them in our assessment in the future and believe such an updated assessment can help achieve sustainability of wood resource.…”
Section: Discussionmentioning
confidence: 99%
“…This biofuel traceability system was designed for agricultural pruning, but could also be adapted for any type of biomass-to-energy initiative to promote the efficient use of renewable energy sources [6]. In this way, it strengthens the efforts of promoting the development of local biomass supply chains for energy production with reduced environmental impact [30].…”
Section: Inspectionmentioning
confidence: 99%